Investigation of the steerable parametric loudspeaker based on phased array techniques - Shi, Chuang (2013)
Due to its ability to generate highly directional sound beams, the parametric loudspeakers are advantageous in creating personal listening zones in public areas. The directivity control of the parametric loudspeaker can provide more flexibility in its applications. This thesis provides an investigation of several practical issues of applying phased array techniques to achieve directivity control in the steerable parametric loudspeaker, and addresses two major problems: (i) spatial aliasing and (ii) mismatches between beampatterns obtained in simulation and measurement. Simulations and measurements are carried out to validate the models and methods proposed in major chapters, based on the simulation framework and measurement setup proposed in the beginning of this thesis. The feasibility of developing the steerable parametric loudspeaker based on phased array techniques is proven in practice. Moreover, a few guidelines are also provided, which can then be applied in many applications of the steerable parametric loudspeaker.